Directive letter from Provincial Sub-Department of Crop Production of Tien Giang on scaling local agro-climatic bulletin development and dissemination in all of its districts - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Technical Working Groups established in Tien Giang and Ninh Thuan for development and dissemination of agroclimatic bulletins. Tien Giang issued directive to scale to 11districts for 2021-22 rice-winter-spring season.